The synthesis and evaluation of quinolinequinones as anti-mycobacterial agents. Issue 16 (15th August 2019) - Santoso, Kristiana T.; Menorca, Ayana; Cheung, Chen-Yi; Cook, Gregory M.; Stocker, Bridget L.; Timmer, Mattie S.M.
Graphical abstract: Abstract: A library of thirty-two quinolinequinones (QQs) with various amine substituents at the 6- and 7-positions were synthesised efficiently and in good yields for evaluation as potential anti-tuberculosis agents. Mycobacterium tuberculosis growth inhibition assays demonstrated that QQs bearing moderate length alkyl chains ( i.e. heptylphenylamino- and octylamino-QQs), and aryl groups ( i.e. phenylethylamino- and benzylamino-QQs) exhibited encouraging inhibitory activity, while QQ analogue 7-chloro-6-propargylamino-quinoline-5, 8-dione (16b ) had excellent inhibitory activity (MIC = 8 μM). The cLogP values and redox activities of the QQs were determined, and neither readout correlated with the anti-mycobacterial activities of the compounds. Notwithstanding, mode of action studies of16b revealed that treatment of M. tuberculosis with this compound led to activation of NADH-dependent oxygen consumption suggesting a redox cycling mechanism. To this end, the promising anti-mycobacterial activity of several QQs and their ability to perturb oxygen management leading to an uncontrolled respiratory burst, as identified in this work and by others, demonstrates the merit of further optimising the anti-mycobacterial activity of this readily synthesised class of compound.